Effects of directional hearing aid settings on different laboratory measures of spatial awareness perception - Micha Lundbeck; Giso Grimm; Volker Hohmann; Lars Bramsløw; Tobias Neher (Audiology Research, 2018)
Hearing loss can negatively influence the spatial hearing abilities of hearing-impaired listeners, not only in static but also in dynamic auditory environments. Therefore, ways of addressing these deficits with advanced hearing aid algorithms need to be investigated. In a previous study based on virtual acoustics and a computer simulation of different bilateral hearing aid fittings, we investigated auditory source movement detectability in older hearing- impaired (OHI) listeners. We found that two directional processing algorithms could substantially improve the detectability of left-right and near-far source movements in the presence of reverberation and multiple interfering sounds. In the current study, we carried out similar measurements with a loudspeaker-based setup and wearable hearing aids. We fitted a group of 15 OHI listeners with bilateral behind-the-ear devices that were programmed to have three different directional processing settings. Apart from source movement detectability, we assessed two other aspects of spatial awareness perception. Using a street scene with up to five environmental sound sources, the participants had to count the number of presented sources or to indicate the movement direction of a single target signal. The data analyses showed a clear influence of the number of concurrent sound sources and the starting position of the moving target signal on the participants’ performance, but no influence of the different hearing aid settings. Complementary artificial head recordings showed that the acoustic differences between the three hearing aid settings were rather small. Another explanation for the lack of effects of the tested hearing aid settings could be that the simulated street scenario was not sufficiently sensitive. Possible ways of improving the sensitivity of the laboratory measures while maintaining high ecological validity and complexity are discussed.